Research of superluminal phenomena revealed the essence and limitation of the relativity - Huaan Zhang; Zihua Zhang (Annals of Mathematics and Physics - Peertechz Publications, 2022)
Superluminal phenomena have been viewed as a contradiction to the Special Relativity, the in-variance principle of light velocity. This paper proposed the theory of the two kinds of epistemology and world, to explain the contradiction between the Special Relativity (SR) and Superluminal phenomena. It also discussed the influence of superluminal research on other science and technology, such as information science and superluminal communications.